Enhanced Production of Aromatic Amino Acids in Tobacco Plants Leads to Increased Phenylpropanoid Metabolites and Tolerance to Stresses - Oliva, Moran; Guy, Aviv; Galili, Gad; Dor, Evgenia; Schweitzer, Ron; Amir, Rachel; Hacham, Yael (Frontiers in Plant Science, 2021)
Aromatic amino acids (AAAs) synthesized in plants via the shikimate pathway can serve as precursors for a wide range of secondary metabolites that are important for plant defense. The goals of the current study were to test the effect of increased AAAs on primary and secondary metabolic profiles and to reveal whether these plants are more tolerant to abiotic stresses (oxidative, drought and salt) and to Phelipanche egyptiaca (Egyptian broomrape), an obligate parasitic plant. To this end, tobacco (Nicotiana tabacum) plants were transformed with a bacterial gene (AroG) encode to feedback-insensitive 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase, the first enzyme of the shikimate pathway. Two sets of transgenic plants were obtained: the first had low expression of the AroG protein, a normal phenotype and minor metabolic changes; the second had high accumulation of the AroG protein with normal, or deleterious morphological changes having a dramatic shift in plant metabolism. Metabolic profiling analysis revealed that the leaves of the transgenic plants had increased levels of phenylalanine (up to 43-fold), tyrosine (up to 24-fold) and tryptophan (up to 10-fold) compared to control plants having an empty vector (EV) and wild type (WT) plants. The significant increase in phenylalanine was accompanied by higher levels of metabolites that belong to the phenylpropanoid pathway. In several lines, the high accumulation of AroG protein was associated with higher levels of anthocyanins and volatility in the flowers. AroG plants showed improved tolerance to salt stress but not to oxidative or drought stress. The most significant improved tolerance was to P. aegyptiaca. Unlike WT/EV plants that were heavily infected by the parasite, the transgenic AroG plants strongly inhibited P. aegyptiaca development, and only a few stems of the parasite appeared above the soil. This delayed development of P. aegyptiaca could be the result of higher accumulation of several phenylpropanoids in the transgenic AroG plants and in P. aegyptiaca, that apparently affected its growth. These findings indicate that high levels of AAAs and their related metabolites have the potential of controlling the development of parasitic plants.